PENGARUH PENDEKATAN PBL BERBANTUAN MEDIA WORDWALL TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS IV PADA MATERI PECAHAN - Rahmadani, Hernadieta; Irawati, Riana; Maulana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Many students struggle with mathematical concepts due to less interactive teaching methods and minimal use of supporting media. This study examines the impact of a PBL approach with Wordwall on grade IV students' understanding of fractions.  Using a quasi-experimental Non-equivalent Control Group Design, 60 students from SD Negeri Sukaraja 1 were selected. Data collection included 10 descriptive test questions and documentation.Results showed the experimental class had a higher average score (81.3) than the kontrol class (62.6), with an n-gain of 0.71 (high) versus 0.36 (moderate) in the kontrol group. This indicates that PBL with Wordwall significantly enhances students' mathematical understanding.Thus, PBL assisted by Wordwall makes learning more interactive and enjoyable, improving students' grasp of mathematical concepts, especially in fractions.